Screening of pathogenic microbiota harbouring antibiotic resistance genes from healthcare wastes in Malaysia : a high-throughput amplicon sequencing approach - Siew, Shing Wei (2023)
The disposal of healthcare waste without prior elimination of pathogens and hazardous contaminants has negative effects on the environment and public health. In past research the microbiological assessment of healthcare wastes employed a culture approach that resulted in the identification of Bacillus sp. in a sample of treated solid healthcare wastes. The effectiveness of microwave in hazardous waste treatment studied based on the survival of tested microorganisms using the culture method may overlook the presence of other pathogens after treatment. Yet, there is scarce data reported on the complete microbial community in microwave-treated healthcare waste using next-generation sequencing technology. This study aimed to profile the complete microbial community, identify viable antibiotic-resistant bacteria in microwave-treated healthcare wastes collected from three different waste operators (FC, FV, and FA) in Peninsular Malaysia, and characterize pathogenic gene markers in isolated organisms. The samples were subjected to bacterial and fungal amplicon sequencing for microbial community characterization, by targeting the full-length 16S ribosomal RNA (rRNA) gene and partial 18S rRNA gene with full-length internal transcribed spacer (ITS) 1 and ITS 2 regions, respectively. Bacterial cultivation was performed to identify viable bacteria in healthcare wastes. The isolated antibiotic-resistant bacteria were subjected to species identification and whole genome sequencing for complete genome characterization. In addition, antibiotic susceptibility testing was performed on the confirmed isolates using the disk diffusion technique to determine the antibiotic resistance patterns. Based on the results of objective 1, the bacterial composition in FC samples was dominated by the Aerococcus, Comamonas, and Pseudomonas genera, while FV and FA were dominated by Bacillus, Paenibacillus, and unclassified Bacilli. All three sets of samples showed significant differences in bacterial diversity, as evidenced by the alpha- (p-value = 0.048) and beta-diversity (p-value < 0.006) analyses. The fungal composition differed significantly between three groups of samples, as evidenced by the alpha- (p-value = 0.045) and beta-diversity (p-value < 0.002). The deep bioinformatic analysis confirmed the presence of blaTEM-1 and penP, which are associated with the production of class A beta-lactamase and beta-lactam resistance pathways. Based on objective 2, the viable bacteria in VFC, VFV, and VFA samples were represented by Proteus, Stenotrophomonas, and Pseudomonas genera, respectively, with significant beta diversity (p-value = 0.003). Based on the BLASTN results, the primary antibiotic-resistant bacteria isolated from VFC, VFV, and VFA samples were Proteus mirabilis, Stenotrophomonas maltophilia, and Pseudomonas sp., respectively. As no specific Pseudomonas species were identified from the database, this bacterium is potentially present as a novel bacterium. For objective 3, P. mirabilis and S. maltophilia were discovered to contain genes associated with virulence function and transposable element expression. The antibiotic resistance genes blaOXA-10 and sul1 were identified in P. mirabilis and S. maltophilia, conferring resistance to beta-lactam and folate pathway antagonist antibiotics. The antibiotic susceptibility tests revealed that P. mirabilis and S. maltophilia were multidrug-resistant bacteria, exhibiting resistance to drugs from multiple classes, including carbapenem. In conclusion, microorganisms and contaminants, which serve as putative indicators in healthcare waste treatment evaluation, revealed the limitations of the microwave sterilization method in microbial inactivation. Our findings suggested that the occurrence of clinically relevant microorganisms, antibiotic contaminants, and associated antibiotic resistance genes represents environmental and human health hazards when released into landfills via horizontal gene transfer.